Influence of host materials on degradation of phosphorescent organic light-emitting diodes under electrical stress. Issue 10 (27th February 2023) - Luo, Jianhui; Wu, Yibing; Lin, Chengwei; Xiao, Shu; Qiao, Xianfeng; Yang, Dezhi; Dai, Yanfeng; Sun, Qian; Chen, Jiangshan; Ma, Dongge
Abstract : The luminance degradation ratio and the corresponding relative change of the exciton lifetimes for different hosts in the resulting yellow PhOLEDs. Abstract : In this paper, the degradation mechanism of phosphorescent organic light-emitting diodes (PhOLEDs) was studied by using different host materials in the emitting layer (EML). Three different types of host materials, including single hosts, exciplex-type co-hosts and exciplex-free co-hosts, were compared in the operation stability against the constant electrical stress, and transient electroluminescence (EL) measurements were used to clarify the origin of degradation by comparing the pristine and degraded PhOLEDs. It was found that the formation of degradation products of exciton quenchers, nonradiative carrier recombination centers and deep charge traps in the EMLs reduces the stability of the resulting PhOLEDs. Our research highlights the need for the development of new highly efficient bipolar exciplex host materials to fabricate more stable PhOLEDs.